1999
DOI: 10.1159/000016956
|View full text |Cite
|
Sign up to set email alerts
|

Are Constipated Children Different from Constipated Adults?

Abstract: Constipation represents a diagnostic category of high prevalence both in children and adults, but with low disability and hospitalization rates. This review is written to be a relatively practical guide to physicians providing information for the evaluation and management of one of the most common chronic digestive disorders. In this article we emphasize the differences between constipation in children and adults. The approach to childhood constipation needs to focus on the behavioral nature of this disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…Vasconcelos et al [20] undertook urinary reeducation in 55 children with LUTD refractory to conventional treatment. Of these, 66% were girls, reinforcing the observations of a higher prevalence of LUTD among girls, as is described in the literature [21][22][23].…”
Section: Discussionsupporting
confidence: 75%
“…Vasconcelos et al [20] undertook urinary reeducation in 55 children with LUTD refractory to conventional treatment. Of these, 66% were girls, reinforcing the observations of a higher prevalence of LUTD among girls, as is described in the literature [21][22][23].…”
Section: Discussionsupporting
confidence: 75%
“…9 The difference in efficacy of the fermented dairy product that contains B lactis DN-173 010 between adults and children underscores the hypothesis that constipation in children differs considerably from that in constipated adults with regard to its prevalence, onset, etiology, symptoms, treatment, and prognosis. 22 We found in the control group a higher rate of success than expected, namely 24% instead of 15%. In an earlier study by Nurko et al 23 conducted in children with functional constipation, a response rate of 40% was found in the placebo group.…”
Section: Discussioncontrasting
confidence: 57%
“…All studies showed an increased defecation frequency and improved stool consistency [20]. These findings, however are not directly applicable to the paediatric population because constipation in children differs considerably from that in constipated adults with regard to its prevalence, onset, aetiology, symptoms, treatment, and prognosis [21]. …”
Section: Discussionmentioning
confidence: 99%